Microstructural modifications in bitumens rejuvenated by oil from pyrolysis of waste tires - Alfe, Michela; Gargiulo, Valentina; Ruoppolo, Giovanna; Cammarota, Francesco; Calandra, Pietro; Oliviero Rossi, Cesare; Loise, Valeria; Porto, Michele; Di Capua, Roberto; Caputo, Paolino (Frontiers in Chemistry, 2025)
IntroductionBitumen is the viscoelastic fluid binding the crushed stones and mineral aggregates in the asphalt material used to pave roads around the world. During the paving procedure, the volatile compounds are lost and oxidization occurs with variation of the mechanical characteristics (aging); thus, the material becomes rigid and brittle over time and may need replacement. Instead of being landfilled, aged asphalts can be reused in new pavements after pretreatment with specific additives to restore their original properties.MethodsBy considering conscious utilization of natural resources, we propose using the condensable fraction (oil) obtained from the pyrolysis of waste tires (WTs) as the agent to rejuvenate aged bitumen. The pyrolysis oil from WTs was produced and characterized using elemental analysis, gas chromatography coupled with mass spectrometry (GCMS), and thermogravimetry. Bitumen was aged by the rolling thin-film oven test procedure and blended with the WT pyrolysis oil at three different concentrations (1%, 3%, and 6% w/w) to evaluate the rheological behaviors. The blends were also investigated using atomic force microscopy, and the asphaltenic fraction was assessed via optical microscopy.Results and discussionAll the data consistently indicate that oil addition not only reduces the viscosity of bitumen and restores it to values close to the original unaged bitumen but also changes the intermolecular structure to recover the self-assembly pattern typical of the unaged sample. The physicochemical mechanisms of this phenomenon are proposed in light of the oil characteristics. Hence, it is concluded that the pyrolysis oil from WTs can be used to rejuvenate asphalts, which can then be used in reclaimed asphalt pavement technology. The impacts of our findings are expected to be extensive because bitumens are globally used for paving roads. In addition, since the proposed method couples/fuses urban waste treatment with asphalt maintenance processes, two types of wastes (oil from pyrolysis of WTs and aged bitumens) can be simultaneously recovered and reused to produce new and performing asphalts.